PPID INSTITUTIONS AND SERVICES IN REGIONAL APPARATUS OF CENTRAL JAWA PROVINCE GOVERNMENT - Pandiangan, Andreas (Universitas Katolik Soegijapranata, 2025)
This study aims to determine and understand the availability of adequate PPID organizations and personnel, the availability of procedures and processes for managing and providing public information services, coordination with other units in a public body. This research method is a qualitative method that seeks to explore the phenomenon of the object of research. The type of qualitative method approach used is a case study. The research location was carried out at 36 PPIDs (Main and Assistant) within the Central Java Provincial Government. Data collection is done through literature studies, regulations and documents. The research found that the latest PPID institutional structure and personnel (2024) are regulated through the Central Java Governor Decree Number 487.22/8 of 2024. The establishment of PPID structure and organization with the division of duties and responsibilities is the actualization of the first element of Gareth R. Jones' (2010) organizational theory, namely differentiation. This includes the implementation of the third element of Gareth R. Jones' organizational theory, namely the existence of an organizational structure. At the same time, the establishment of the PPID organization also regulates coordination and communication between units within the public body and coordination and communication between PPID organs when implementing public information services. This is the implementation of the second element of Gareth R. Jones' organizational theory, namely integration. The existence of the PPID SOP and the dissemination of public information is more effectively and efficiently done through the website than by other means.